Ethno-religious conflicts in North-Western Nigeria: the case of Kaduna State - Umar, Nasiru (2017)
Conflicts, especially in a democracy, are normal within the confines of democratic rules, but where they become persistent and especially violent; the social system requires an indepth study to establish the reasons. Nigeria has been grappling with persistent ethnoreligious crises that have taken the lives of thousands, destroyed an indeterminate value of properties, and displaced millions of people including women and children resulting in democratic instability in the country. The recurrent violent confrontations that have continued unabatedly among ethnic groups in the North Western geopolitical zone particularly Kaduna state for over a decade and that seem to be on the increase especially with the democratization of the polity necessitate a critical examination to fathom the underlying factors responsible for the incident. The study intends to find out whether ethnicity and religion impacts on justice and political tolerance and whether cultural diversity is a factor in the unending confrontations. The research selected three important flashpoints within the state-Kaduna metropolis, Kafanchan, and Zangon kataf for study. In-depth interviews were conducted with participants whose responses were organized and managed using the Nvivo 11 software for subsequent analysis. Three key findings were found: (a) ethnoreligious conflicts are the outcome of an elite power struggle which denies citizens justice through the manipulation of religion and ethnicity; (b) the manipulation of ethnic and religious identities by the politicians has made the two communities exclusive, rendering them intolerant; and (c) that cultural diversity is used by ethnic groups to make demands on government lo the exclusion of others with whom they do not share cultural affinity thus promoting social exclusion and violent resistance from the marginalized communities. The study contributes to the understanding of social justice and political tolerance as important variables in the development of political culture.